Dependence of microstructures on fatigue performance of polycrystals: A comparative study of conventional and additively manufactured 316L stainless steel. (February 2022) - Cui, Luqing; Jiang, Fuqing; Peng, Ru Lin; Mousavian, Reza Taherzadeh; Yang, Zhiqing; Moverare, Johan
Highlights: Fatigue properties and microstructural evolution of AM steel were systematically studied and compared with its wrought counterpart. Unique microstructures of AM steel contribute greatly to its superior fatigue property, and underlying mechanisms were studied. Pre-existing high-density dislocations and chemical microsegregation in AM steel partly contribute to its superior fatigue property. The enhanced planar slip by its unique microstructures in AM steel plays an additional role in the superior fatigue property. The unique cell structure has more positive effects on LCF performance of AM steel due to the enhanced ductility. Abstract: The fatigue properties and microstructural evolution of 316 L stainless steel (316LSS) manufactured by laser powder bed fusion (L-PBF) were systematically studied and compared with its wrought counterpart. The as-built L-PBF 316LSS shows a pronounced heterogeneity, not only structurally but also chemically, with a unique microstructure of highly serrated grain boundaries, bimodal grain structure, nano-precipitates, solidification cell structures, and chemical segregations. The microindentation test showed that the hardness of the as-built L-PBF 316LSS reached 2.589 GPa, which was about 1.6 times higher than that of the wrought solution annealed counterpart, and the sparser slip steps around indentations revealed its greater dislocation storage capability. The S-N curves indicated that the fatigue resistance of the as-built L-PBF 316LSS was significantly better than that of the wrought solution annealed samples, and this was ascribed to its unique microstructural characteristics, especially the pre-existing high-density dislocations and chemical microsegregation within cellular solidification features. Furthermore, the enhanced planar slip in L-PBF 316LSS by its unique microstructure, especially the formation of deformation twins, delays the strain localization and restrains slip band generation, thereby significantly inhibiting crack initiation, and contributing greatly to the fatigue performance. The unique cell structure appears to be more effective in improving the low-cycle fatigue performance of L-PBF 316LSS due to the enhanced ductility.